Aortic Knob Diameter in Chest Radiographs of Healthy Adults in Uganda - Magera, Steven; Sereke, Senai Goitom; Okello, Emmy; Ameda, Faith; Erem, Geoffrey (Informa UK Limited, 2022)
Background The burden of cardiovascular diseases, such as aortic and degenerative diseases, grows in the aging population. Chest radiograph still plays an important role in the diagnosis of cardiovascular diseases. Aortic knob diameter in chest radiographs can be used to evaluate early changes of the aortic structure and together with clinical and laboratory findings. This study was aimed at determining the mean values of aortic knob diameter among healthy adults in Uganda. Methods We conducted a descriptive cross-sectional study in three selected hospitals in Kampala Uganda. All participants had normal chest radiographs without radiological evidence of cardiovascular disease. Chest radiograph findings extracted included aortic knob diameter, aortic arch diameter, transverse heart diameter, and transverse thoracic diameter. All films were independently examined by two experienced radiologists. Results We analyzed chest radiograph findings of 294 participants, of which 204 (69.4%) were male. Aortic knob diameter increased with age (p – 0.000). The mean aortic knob diameter of males was higher than for females (3.14±0.34cm versus 2.77±0.37cm, p – 0.000). The mean aortic knob diameter on the digital screen was higher than plain films (3.03±0.393cm versus 2.96±0.392cm, p – 0.000). Aortic knob diameter positively correlated with age (p – 0.000) and aortic arch diameter (p – 0.000). Aortic knob diameter also correlated positively with a transverse thoracic diameter (p – 0.05), transverse heart diameter (p – 0.05), and cardiothoracic ratios (p – 0.05). Conclusion The aortic knob diameter was higher in males and there was a positive correlation with age, aortic arch diameter, transverse heart diameter, and transverse thoracic diameter. Aortic knob diameter measurements should be done on digital rather than printed x-ray films.